Cerebellar hemangioblastoma with perivascular pseudorosette formation and glial differentiation: A case report. Issue 2 (24th August 2016) - Wang, Jian; Lin, Xu‐Yong; Qiu, Xue‐Shan; Wang, En‐Hua; Yang, Lian‐He; Yu, Juan‐Han
Abstract : Hemangioblastoma is a well‐circumscribed, highly vascular, lipid‐rich and low‐grade tumor of uncertain histogenesis. Its histopathological features have been well established. Herein, we present a case of cerebellar hemangioblastoma in a 43‐year‐old woman. Histologically, the tumor was predominantly composed of cellular areas showing eosinophilic or vacuolated stromal cells arranged in nests and sheets. Focally, conventional reticular areas could be seen. Additionally, in some areas, the stromal cells were arranged radially around blood vessels, exhibiting perivascular pseudorosette structures, which were similar mostly to those of ependymomas. Immunohistochemically, the stromal cells markedly showed diffused staining for Vimentin, S‐100, CD56, NSE, inhibin‐a, podoplanin, alpha‐Thalassemia/mental retardation syndrome X and carbonic anhydrase IX, and were negative for cytokeratin, epithelial membrane antigen, oligodendrocyte transcription factor 2, neuronal nuclear antigen, synaptophysin, isocitrate dehydrogenase 1 (R132H), P53 and CD34. Interestingly, the reticular and cellular areas either showed no or individual scattering of the GFAP‐positive cells, respectively, while, the perivascular pseudorosette areas strongly and diffusely expressed GFAP. Nuclear mitosis and necrosis were not observed. The MIB‐1 antibody labeling index was especially low (about 3%). Based on these findings, the patient was diagnosed with cerebellar hemangioblastoma. In the present case, we documented a distinctive histological appearance of perivascular pseudorosettes in hemangioblastoma and provided the evidence for stromal cells with glial differentiation.